Productivity Analysis in Garments and Textile Industries - Caesar B. Cororaton (Philippine Institute for Development Studies (PIDS), 1997)
While the textile industry has been performing below par due to various factors, the garment industry has exhibited contrast despite weak support from other industries. Analysis shows that some of the sub-industries in the textile industry are technically inefficient but its output can be augmented given improvement in its organizational set-up. Garment industry, on the other hand, requires upgrading of existing technologies and the human skills associated with it to reap a positive technical efficiency contribution to total factor productivity.
Keywords: 330; productivity; garments and textile industries; total factor productivity; technical efficiency